MON-275 Prolactin to Testosterone Ratio Predicts Pituitary Pathology in Hypogonadal Men with Mild Hyperprolactinemia - Naelitz, Bryan D (J Endocr Soc, 2020)
Background: Serum prolactin (PRL) and testosterone (T) levels are routinely evaluated in men presenting with clinical symptoms of hypogonadism. Persistent mild elevations in PRL are often benign, but may reflect structural pathology. Though pituitary magnetic resonance imaging (pitMRI) is often obtained to assess for anatomic lesions, it remains unclear how to optimize screening in hypogonadal men with mild hyperprolactinemia. Objective: We sought to identify risk factors associated with detection of pituitary pathology among hypogonadal men with mild hyperprolactinemia and aimed to improve selection of those indicated for pitMRI. Methods: A retrospective, case-control study was performed. Men under 75 presenting with clinical hypogonadism and mild hyperprolactinemia (15-50 ng/dL) who underwent pitMRI at a single tertiary care center were included. Individuals presenting with clinical symptoms strongly suggestive of a pituitary mass (e.g. visual change, headache, panhypopituitarism) were excluded, as were patients who had been previously evaluated for hyperprolactinemia. Age, body mass index (BMI), presenting symptoms, prescription history, and pitMRI findings were abstracted from the electronic medical record. Results: 141 men met inclusion criteria. A minority exhibited pituitary pathology (n=40, 28%) with adenoma being the most common finding (n=35, 88%). Empty sella variants and non-neoplastic cysts comprised the remainder of pathologies (n=5, 12%). Mean PRL was higher in men with pituitary pathology than in controls (27.2 vs. 23.3 ng/mL; p=0.0106), while mean T levels were lower (190 vs 287 ng/dL; p=0.0001). Mean PRL/T ratio values were greater in cases (0.34 vs. 0.08; p<0.0001), as were median values (0.15 vs. 0.09). PRL/T outperformed PRL or T in predicting positive pitMRI findings (AUC: 0.75 vs. 0.64 vs. 0.71, respectively). A PRL/T ratio >0.08 was 90% sensitive, detecting 36/40 lesions, and 42% specific, excluding 42/101 patients with normal anatomy (p=0.0003). If applied to the study cohort, this cutoff would have reduced pitMRI burden by 30%. Ordering pitMRI when the PRL/T ratio >0.08 or when PRL >25 increases sensitivity (98%, 39/40 lesions detected) at the cost of decreased specificity (32%, 32/101 controls excluded). Presenting symptoms including fatigue, decreased libido, erectile dysfunction, and gynecomastia did not vary between cases and controls. Though patients with pituitary lesions were more likely to receive dopamine agonists than controls (40% vs. 23%; p=0.0392), they were not more likely to be prescribed testosterone, antipsychotics, or antidepressants. Conclusions: The PRL/T ratio is superior to PRL or T alone in identifying pituitary pathology in hypogonadal men with mild hyperprolactinemia. Ordering pitMRI when the PRL/T >0.08 is sensitive for detecting pituitary lesions and may reduce pitMRI burden in this population by 30%.